A COMPARATIVE STUDY ON THE INCIDENCE OF TICKS AND TICKS BORN DISEASES ON LOCAL AND CROSSBRED CATTLE IN MALAKAND AGENCY - N. Ahmad; H.A Hashmi (Journal of Animal and Plant Sciences, 2007)
Ticks infestation and piroplasmosis are serious problems of domestic cattle. The present study was conducted to find out the prevalent species of ticks and the piroplasms transmitted by these ticks. The effect of ticks and blood parasites on various blood parameters was also studied. The parameters included: TEC count, TLC count, haemoglobin (Hb) estimation, erythrocytic sedimentation rate (ESR) and differential leukocytic count (DLC). The study was conducted from June to August 2001. A total of 80 cattle (40 local nondescript cattle and 40 crossbred) were selected. Each type was divided into four groups A, B, C and D. The cattle of group—A were free from any infestation/infection. The animals of group B were only tick infested. Animals of group—C were only piroplasm infected and the animals of group—D were infested with ticks and the piroplasms infected. Each group from both the genetic groups consisted of 10 animals. HaemotologicaI examination revealed a significant decrease (P<0 .05) in TEC, Hb and TLC in groups B, C and D as compared to group—A relating to each genetic group. The lymphocytes were decreased from normal in all test groups in both the genetic groups, significantly. However, neutrophil and eosinophils were increased significantly in test groups as compared to control group (A). The values of erythrocytic sedimentation rate (ESR) showed a significant increase in groups B, C and D of both types of cattle as compared to the control group (A). The overall results showed that the effect of mixed infection on haematology was greater than the single infection of ticks or piroplasm.
Keywords: Ticks; Erythrocytic sedimentation rate (ESR); differential lenkocytic court (DLC); lymphocytes